PENERAPAN ERGONOMI PADA PEKERJA MANUAL MATERIAL HANDLING DENGAN METODE OWAS DAN NBM UNTUK MENINGKATKAN PRODUKTIVITAS PEKERJA DI PT. ATAK - Annisa Putri Aulia; Markus Hartono; Sritomo Wignjosoebroto (CALYPTRA, 2018)
This study discusses the activity of Manual Material Handling (MMH) to workers in the painting division to support the movement of goods. MMH activity has an increased risk of Musculosceletal Disorders (MSDs). To conduct a working attitude analysis, the Ovako Working Analysis System (OWAS) method is used by conducting initial observation and taking photos/videos when the worker performs the MMH activity. Then interviewed 5 workers in the painting division using the Nordic Body Map (NBM) questionnaire to find out the level of pain complaints felt by workers. Furthermore, the calculation of productivity to find out the standard output by collecting data processing time of MMH activity from the painting division. Data retrieval, data processing and analysis results done before and after implementation. Implementation is done is the addition of tools such as hanging rails and pulleys that can ease the activity of MMH and improve work productivity in the painting division. Based on the data processing and analysis results that have been done, the number of MMH activity done by the worker decreased from 6 activities to 5 activities, the level of the sickness that was felt by the workers was down from 2.86% to 1.20%. This makes the standard output increase from 0.270 to 0.593. The number of work productivity increased from 21,096 to 77,034 with value of productivity index ratio is 0,274. This shows that there is a significant increase in productivity.